Metastatic type A thymoma: morphological and genetic correlation - Bürger, Thomas; Marx, Alexander (Histopathology, 2017)
Aims The vast majority of type A thymomas are diagnosed in tumour stages 1 or 2, and metastatic cases are exceedingly rare. The histological and genetic features of such metastatic type A thymomas have not been described in detail. Methods and results Five metastatic type A thymomas in tumour stage Masaoka IVb that had been reviewed by a panel of expert pathologists were analysed using comparative genomic hybridization (CGH). Cases 1, 2 and 3 showed the prototypical morphology of type A thymomas with mainly solid growth patterns. These cases displayed only very subtle nuclear irregularities and slight nuclear crowding, but no other atypical features. Mitoses were absent. Cases 3 and 4, in contrast, had a distinctly atypical morphology. CGH revealed partially recurrent alterations in four cases (with and without atypical morphology), including gains on chromosome 1q (one case), 17q (two cases), chromosome 19 (three cases) and 22q (one case) and losses on chromosome 17p (two cases) and 22q (one case). Conclusion Rare metastatic type A thymomas, both with typical and ‘atypical’ histological features, show partially recurrent genomic alterations that differ from the much more frequent localized and indolent tumours. The fact that these alterations were recurring points to a link between clinical behaviour and molecular features. Our findings may have implications for the management and treatment of such tumours.